2013
DOI: 10.4103/2229-516x.117086
|View full text |Cite
|
Sign up to set email alerts
|

Study of platelet aggregation in acute coronary syndrome with special reference to metabolic syndrome

Abstract: Background/Context:Antiplatelet drug resistance increases the risk of adverse events like stent thrombosis in acute coronary syndrome (ACS). Metabolic syndrome (MS) is a prothrombotic state and presence of MS further increases the risk of antiplatelet drug resistance.Aims and Objectives:We studied platelet aggregation characteristics in patients of ACS for aspirin or clopidogrel resistance. We studied the relation of drug resistance with blood markers like high sensitivity C-reactive protein (hsCRP). We also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Such data suggest that diabetes is associated with considerable resistance to aspirin and clopidogrel therapy, and such insufficient antiplatelet responses could be an underlying causal factor for the frequent END observed in this population. In accordance with the elevated fibrinogen levels in our data, a recent study evaluating platelet aggregation characteristics in acute coronary syndrome found antiplatelet drug resistance to be significantly associated with metabolic syndrome, and fibrinogen levels and high sensitivity-CRP were higher in this population [ 37 ]. Serum fibrinogen levels appeared to be strongly associated with drug resistance [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…Such data suggest that diabetes is associated with considerable resistance to aspirin and clopidogrel therapy, and such insufficient antiplatelet responses could be an underlying causal factor for the frequent END observed in this population. In accordance with the elevated fibrinogen levels in our data, a recent study evaluating platelet aggregation characteristics in acute coronary syndrome found antiplatelet drug resistance to be significantly associated with metabolic syndrome, and fibrinogen levels and high sensitivity-CRP were higher in this population [ 37 ]. Serum fibrinogen levels appeared to be strongly associated with drug resistance [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…High levels of resistance to antiplatelet drugs were determined in MS patients. ACS patients without MS also showed this resistance to a significant degree ( 17 ). In 2009 Massie BM et al carried out the treatment applying warfarin and clopidogrel or aspirin during a period of 30 months.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, platelets do have direct collagen receptors (GP VI and integrin α2β1) on their surface that does not require vWf for collagen binding with GP VI playing a major role in platelet activation upon collagen binding. Collagen was applied in these experiments in similar concentration as used in light transmission aggregometry . It is possible that—despite the intentionally lowered platelet count in samples—collagen actually triggered platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen was applied in these experiments in similar concentration as used in light transmission aggregometry. 17 It is possible that-despite the intentionally lowered platelet count in samples-collagen actually triggered platelet aggregation. The total surface of platelet aggregates is much smaller than the combined surface of individual adhering platelets which accounts for the decrease in impedance.…”
Section: Impedimetric Platelet Adhesion and Spreading Measurementsmentioning
confidence: 99%